DAMPAK EKONOMI FLU BURUNG TERHADAP KINERJA INDUSTRI PERUNGGASAN DI PROVINSI JAWA TENGAH - -, SAPTANA; BASUNO, EDI; YUSDJA, YUSMICHAD (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Avian Influenza (AI) is poultry infectious disease and can cause dead. Apart from that, as a whole, AI has significant socio-economic impacts on poultry industry. In general, this particular study aims to observe economic impact of AI towards performance of poultry industry in Central Java Province. Economic impact caused by AI towards poultry industry varies from region and from the type of poultry. The most suffer was experienced by quail and layers farms, while impact on broilers relatively small. Integrated type of farms suffered more compared to independent farms that spread out with a better natural barrier. On breeding farms, AI had reduced DOC production to 40 percent and also reduced DOC selling price far below break even point (BEP). On feed industries, 14, 58 percent reduction on production was occurred, however, it does not have impact on feed selling. Meanwhile, economic impact of AI towards chicken slaughtering house, broiler middlemen and retailers reduced by 40, 80 and 33 – 50 percent respectively and it has impact on temporary selling price. Economic impact of AI towards egg middlemen and egg retailers also decreased by 66, 67 and 53 percent respectively, however it did not influence egg selling price. Relevant policy implications are: (1) implements early detection; (2) applies quick and accurate data monitoring; (3) implement tight bio-security; (4) recovery policies at the farm level, with compensation and low interest rate credit supports.
Keywords: Avian Influenza (AI), economic impact, poultry industry